The integration of music with reading concepts to improve academic scores of elementary students - Lyons, Linda M., author; Quick, Don, advisor (Colorado State University. Libraries, 2008)
The purpose of this research was to investigate the effect of an integrated music curriculum on human learning, focusing on reading achievement. To determine if this technique would make a difference, an experimental design was employed, with a measurement of growth rate in reading skills. The curriculum was delivered, via recorded DVD lessons, to 49 second graders. The majority of the students participating in the study were either Caucasian (50%) or Hispanic (37.5%). One class received the intervention, and one was designated as a wait-list control group which received the intervention during the second half of the semester. This design allowed all students to receive the intervention and added to the effective sample size (N = 56), thereby increasing the power of this research. A nationally-normed, standardized reading achievement test, the Predictive Assessment of Reading (PAR), administered before and after each intervention, was the primary instrument used to assess gains in reading achievement levels. A comparison of pretest-posttest gain scores revealed that students in the intervention groups, on average, scored significantly higher on all six subtests of the posttest. In addition, there was a statistically significant difference between the control group and the combined intervention groups on the gain scores of one subtest. A comparison of the two separate intervention groups with the control group showed that the overall F's for two of the six PAR subtests were significant. Simple effects post hoc analyses also revealed that Hispanic students in the intervention groups had significantly higher picture recognition gain scores than Hispanic students in the control group. The researcher believes that this holistic music intervention contains many of the elements of brain-compatible learning, and positively affected the outcome of reading achievement scores. Bringing music into the classroom enabled students to connect ideas being introduced in the music lessons, with concepts taught in their other classes. Through integrated lessons, students developed active listening skills, phonemic awareness, language and graphing skills. Teachers reported that students were engaged in the process and found it memorable. This is substantiated by the finding that gains were made on all subtests, by the intervention groups.
Keywords: academic scores; brain-compatible; contextual learning; elementary curriculum; elementary students; interdisciplinary; multiple intelligences; music; reading concepts; elementary education; literacy; curriculum development; music education; achievement tests; elementary school students